Usage of starter cultures as inhibitors of microbiological hazards in fermented meat products - Pejkovski, Z., Silovska Nikolova, A. (Knowledge - International Journal, 2023)
A large number of food poisonings occur worldwide due to hygienic, toxicological and other food contaminants. They imply consequences that endanger the health and safety of consumers and, furthermore, result in economic losses. Food sold on the market must meet the basic criteria for good hygienic and manufacturing pracitices, as well as the food safety requirements. Meat and meat products are one of the most common sources of foodborne diseases due to a large number of possibilities for contamination from foodborne pathogens during processing, storage, transportation, etc. In the contemporary industry of meat, besides the usage of preservatives and good hygienic and manufacturing practices, the usage of starter cultures, as inhibitors of microbiological activities, has become increasingly important, as well. The usage of starter cultures contributes to the inhibition of growth and proliferation of pathogenic microorganisms. Lactic acid bacteria (LAB) create a large number of antimicrobial metabolites. The most common, between them, are: organic acids, bacteriocins, diacetates, hydrogen peroxide, carbon dioxide, etc. They create unfavorable conditions for the activity of unwanted microorganisms. Coagulase-negative staphylococci have the ability to reduce the nitrate to nitrite. Nitrites have antimicrobial properties.
Keywords: pathogenic microorganisms, safety, inhibitors, starter cultures, lactic acid bacteria